Human papillomavirus vaccination uptake among childhood cancer survivors in Western New York. Issue 11 (12th September 2022) - Garcia, Melany; McGillicuddy, Cailey; Rodriguez, Elisa M.; Attwood, Kristopher; Schweitzer, Jennifer; Coley, Scott; Rokitka, Denise; Schlecht, Nicolas F.
Abstract: Introduction: The risk of human papillomavirus (HPV)‐associated cancers is significantly higher among survivors of a childhood cancer compared to the general population. Despite this, their HPV vaccine uptake rates are lower. We examined factors related to HPV vaccine uptake among childhood cancer survivors from Western New York over 13 years following the introduction of HPV vaccines. Methods: Retrospective review of patients diagnosed with invasive or noninvasive cancerous conditions at age 9 or younger treated at Roswell Park Oishei Children's Cancer and Blood Disorder Program. We matched vaccine date information for patients aged 9–26 years between 2006 and 2020 from the New York State Immunization Information System. Demographic and cancer‐related information was abstracted from electronic medical records. Cumulative vaccine uptake was assessed by Kaplan–Meier and Cox proportional hazards regression models. Results: A total of 284 patients were included in the analyses. Most were non‐Hispanic/White (80.3%) and resided in a metropolitan area (81.7%). Approximately half had leukemia or lymphoma (54.9%), and most received chemotherapy. Females were more likely to initiate the HPV vaccine and did so sooner (median = 5.5 years) than males (median = 5.7 years; log‐rank p  = .301). Patients who were older at vaccine eligibility and males who received blood product transfusions were significantly less likely to initiate the HPV vaccine. Conclusion: While rates of HPV vaccine initiation have been increasing with time among childhood cancer survivors, they remain low overall, with differences seen by treatment and diagnosis. Our findings support the need for further research to optimize HPV vaccine delivery in cancer care.